Memory - Kemp, S (Routledge, 2022)
The failings of Proust’s other kind of memory, voluntary memory, are very much to the fore in the novel; indeed, failure seems to be its principal characteristic. Proust’s most sustained and systematic discussion of memory comes right at the start of In Search of Lost Time in the run-up to the madeleine episode, where the Narrator explains his theory of voluntary and involuntary memory. Involuntary memory restores past experience to the present mind in a way that not only spans the gap of years between them but abolishes the gap as if abolishing time itself. Proust’s conception of memory is founded upon the double experience of involuntary memory, which brings together the past and present in a moment of vivid recollection, while unlocking an essence of experience or a law of human nature through their elements of unity.